IDEF-0 Framework: Developing New Method of Self-Managed Procurement Type1 in Construction Project - Fauziah, Asyiqarizqi (Proceedings of the International Conference on Green Technology; Vol 14 No 1 (2024): Proceeding of 14th International Conference on Green Technology, 2024)
Indonesia Public Procurement has introduced a new method of Self-managed Procurement Type-1 for construction projects. This method is designed specifically for small to medium-sized construction projects that can be managed independently. The research aims to develop a conceptual framework using the IDEF-0 analytical method. The method uses qualitative descriptive and data collection from a case study analysis of a government project. The result is a conceptual framework model of the New Self-managed procurement method. It comprises three stages which generate a process model including preparation, implementation, and supervision. The framework could be implemented and adopted by the industries, as well as the institutions and government agencies.